Playing possum [large type] - Schmitt, Lois (A Kristy Farrell mystery, 2022)
"When animals start mysteriously disappearing from the Pendwell Wildlife Refuge, former English-teacher-turned-magazine-reporter Kristy Farrell is on the case. Days later, the body of the refuge's director is found in a grassy clearing. Kristy, assisted by her veterinarian daughter, investigates and discovers strong motives among the suspects, including greed, infidelity, revenge, and blackmail. As Kristy delves further, she finds herself up against the wealthy and powerful Pendwell family, especially matriarch Victoria Buckley Pendwell, chair of the refuge's board of trustees, and Victoria's son, Austin Pendwell, who is slated to run for state senate. But ferreting out the murderer and finding the missing animals aren't Kristy's only challenges. While researching a story on puppy mills, she uncovers criminal activity that reaches far beyond the neighborhood pet store. Meanwhile, strange things are happening back at the wildlife refuge, and soon a second murder occurs. Kristy is thwarted in her attempts to discover the identity of the murderer by her old nemesis, the blustery Detective Wolfe. Kristy perseveres, and as she unearths shady deals and dark secrets, will she succeed in drawing the killer out of the shadows?"--